O processo de (des)territorialização do povo Kajkwakratxi (Tapayuna) na região do rio Arinos e a remoção compulsória para o Parque Indígena do Xingu (PIX) - Stetiski, Edinei (2023)
The object of this research is the Ministry of Finance case No. 0768.36.754 of 1977, which resulted in the extinction of the "Tapayuna Indigenous Reserve", created by decree No. 63.368 of October 8, 1968. This is an immersive study into the dramas, memories and resistance of the Tapayuna people, whose history is traversed by the hegemonic project of economic development in the state of Mato Grosso, which began in the second half of the 20th century. In this dissertation, I try to show that, in a short space of time, the Tapayuna saw their traditional territory deliberately invaded by migrants who arrived in the region attracted by the possibility of access to land. A process of land-grabbing legitimized by the state itself resulted in profound impacts on the way of life of the survivors who were contacted, such as the process of dispossession from their traditional land located in the northwestern region of the state of Mato Grosso to the Xingu Indigenous Territory (TIX). In order to analyze the process of nullification and extinction of Decree No. 63.368 of October 8, 1968, which established the "Tapayuna Indigenous Reserve", it was necessary through this bibliographic research to reconstruct the historical crossings that marked the Tapayuna people's way of life from the first contacts with national society to the reterritorialization of the survivors to the Xingu.